Bla-OXA48 gene microorganisms outbreak, in a tertiary Children's Hospital, Over 3 years (2012–2014): Case Report. Issue 40 (October 2017) - Herruzo, Rafael; Ruiz, Guillermo; Perez-Blanco, Veronica; Gallego, Sara; Mora, Eduardo; Vizcaino, Maria Jose; Omeñaca, Felix
Abstract: Rationale: Carbapenem-resistant Enterobacteriaceae are an emerging problem in children. Nosocomial spread remains the principal risk factor for acquisition of these microorganisms. Patients concerns: We describe an outbreak of Klebsiella pneumoniae OXA48 (KOXA48) in a tertiary children's hospital during the years 2012 to 2014, as well as the preventive measures put in place in colonized and infected cases. Diagnoses: We studied, "in vitro, " the KOXA48 susceptibility to antiseptics and surface disinfectants. Moreover, an epidemiological surveillance of infection or colonization by these microorganisms, with molecular typing of the KOXA48, was performed, and carbapenemase genes were confirmed by polymerase chain reaction (PCR). Interventions: The bundles recommended (early detection, cohorting of children and health care workers [HCW], contact precautions, etc.) to control the KOXA48 outbreak were taken from those described in the centers for disease control (CDC) 2012 guide, and adapted according to our experience in controlling other outbreaks. Outcomes: All the KOXA48 microorganisms isolated from children belonged to the same strain (ST11) and were susceptible to alcohol solutions but not the surface disinfectant previously employed in our hospital (tensoactive). We reinforced the surface disinfection using a double application (tensoactive + alcohol). The outbreak of KOXA48 begun in 2012 (16 cases in neonatal intensive care unit [NICU] and 1 in pediatric intensive care unit [PICU]) ended before the end of the same year and was not transmitted to new patients in 2013 to 2014, despite readmission of some colonized cases, in intensive care units (ICUs) and other units, of our children hospital. Lessons: Infected children are the tip of the iceberg (3/17) of KOXA48 prevalence making it necessary to identify the cases colonized by these bacteria. At the beginning of the outbreak, the susceptibility of the epidemic strain to antiseptics and surface disinfectants should be studied. Moreover, the measures taken (cohorts, contact precautions, etc.) must be thorough in both colonized and infected cases, immediately, after microbiological diagnosis.